Issuing stock recommendations: Theory and evidence - CHEN, Xia (Institutional Knowledge at Singapore Management University, 2003)
In this paper, we investigate determinants of the market impact of stock recommendations issued by sell-side financial analysts. We propose a simple framework for understanding the process that financial analysts use to issue stock recommendations. The framework yields three testable predictions: The market impact of stock recommendations increases with analysts' perceived ability and investors' uncertainty about firm value, and decreases with analyst experience after controlling for analysts' innate ability. We empirically test these predictions and find consistent results. Using Institutional Investor All-American analyst status to proxy for high perceived ability and return volatility for uncertainty about firm value, we find that the market impact of recommendations increases with analysts' perceived ability and return volatility. Using the number of quarters an analyst has been issuing recommendations or earnings forecasts to proxy for experience, we find that the market impact of recommendations decreases with analyst experience after controlling for analyst-company specific effects. These results hold when we control for other characteristics of financial analysts and brokerage firms that might affect the market impact of stock recommendations. The results hold for recommendation revisions as well.